Intravenous Administration of sRNA Nanoparticles for Treatment of Osteoporosis in Mice - Xuemeng Mu; Xinyi Du; Huitian Han; Fei Liu; Zhifa Zheng; Jing Hao; Lijin Liu; Su Liu; Ze Wei; Changfa Huang; Annan Liang; Wei Zou; et al. (Pharmaceutics)
Background: With the intensification of population aging, osteoporosis has become one of the significant public health issues affecting human health. Currently available medications for treating osteoporosis are associated with various adverse effects and resistance issues. Oligonucleotide drugs show great potential. Effective delivery systems are essential to enhance the stability, bioavailability, and targeting of sRNA drugs. Lipid nanoparticles (LNPs) show promise as alternative osteoporosis therapeutics. This study explores the potential of LNPs as an effective delivery system to treat osteoporosis. Methods: LNPs were prepared using microfluidic techniques with varying lipid compositions, and characterized in terms of size, zeta potential, and entrapment efficiency (EE%). Dynamic light scattering (DLS) was employed to determine the size of the LNPs. The zeta potential was measured using electrophoretic light scattering. The pharmacodynamic effects and safety were then evaluated in a mouse model through intravenous administration. Results: Several lipid nanoparticle (LNP) formulations with different nitrogen/phosphorus ratios and different DMG-PEG2000 ratios were examined, and a lead candidate that supports delivery of sRNA in animal models of osteoporosis was identified. In OVX mice, LNP-sRNA significantly improved bone mineral density (BMD), trabecular microstructure, and biomechanical strength. Safety assessments revealed no systemic toxicity. It is shown that the optimized LNPs can serve as a promising delivery system to mediate sRNA delivery to bone tissue. Conclusions: After comparison of in vitro and in vivo properties, the optimized LNPs demonstrated good comprehensive performance as a delivery system for osteoporosis treatment. These results highlight the potential of the optimized LNPs as an ideal delivery system for osteoporosis, offering improved therapeutic efficacy and reduced systemic side effects.